Analisis Bibliometrik Kompetensi Insinyur Teknik Lingkungan Keahlian Pengelolaan Limbah Padat - Sumarlin, Sumarlin; Sukamta, Sri; Basyrun, Basyrun (Universitas Muhammadiyah Kendari, 2026)
Research on environmental engineering competencies in solid waste management remains fragmented and primarily focused on technical aspects. This study maps the evolution of this field using a quantitative bibliometric approach. Bibliographic data were retrieved from Google Scholar via Publish or Perish (PoP) using the query